(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
Falls among the elderly pose a significant health risk, leading to injuries and decreased quality of life. This article examines the crucial role of physiotherapy and nursing teams in preventing falls in the elderly population. Through comprehensive assessments, personalized interventions, and patient education, these teams address individual risk factors and implement strategies to enhance strength, balance, and mobility while mitigating environmental hazards. By collaborating closely and empowering patients and caregivers, physiotherapy and nursing teams contribute to reducing fall incidence and improving overall well-being in elderly individuals.